ELIXR furthering technological research and development Through a beta-generative Eduspace for Learning and Instruction of eXtended Reality - De Guzman, Jenina G.
Extended reality (XR) is a booming technology all over the world with several uses in various fields. In the Philippines, it is yet to become mainstream, so despite its untapped potential in the industry and market, XR remains underutilized in the country due to the lack of awareness of the general public about its uses, purposes, and possible aids, therefore hampering its developmental use for interested industries, not to mention being accessible and known only to a select few people. Furthermore, this lack of awareness, together with how much other foreign characters have gradually been seeping their way towards XR use in their respective countries, indicates a division in the people’s knowledge for the advantages when using XR and the reality of knowledge lapses in this immersive technology. To venture in this field, this project aims to design a research center within the educational and civic premises of the University, which is projected to utilize existing XR technologies, teach XR to interested individuals, and research further on XR to maximize its potential as much as possible, especially to provide edutainment to its users. This is also anchored on the concept of citizen science and taking into consideration, specifically as a university setting-focused design, digital pedagogy for higher education institutions (HEIs) using XR. The aim, therefore, is to bridge this division in an architectural lens that facilitates space and technology while balancing relevance with timeliness, attempting to eliminate, let alone reduce, the risk of obsolescence in a perpetually advancing technological society.